INVITRO α- AMYLASE AND α- GLUCOSIDASE INHIBITORY ACTIVITIES OF THE ETHANOLIC EXTRACT OF DIOSCOREA VILLOSA TUBERS. - ANITHA ROY; R.V GEETHA (International Journal of Pharma and Bio Sciences, 2013)
The objective of this study was to evaluate α- amylase inhibitory and α – glucosidase inhibitory activity of the ethanolic extract of Dioscorea villosa tubers in vitro. Different concentrations of the plant extract (1.5, 3, 7, 15.30, 60, 125, 250, 500 and 1000 μg/ml) were prepared in ethanol and subjected to α amylase inhibitory and α Glucosidase inhibitory assay. The absorbance was read at 540nm and 546nm respectively using spectrophotometer. Using this method, the percentage of α - amylase inhibitory activity, α -glucosidase inhibitory activity and the IC50 values of each assay were calculated. Results: The ethanolic extract of Dioscorea villosa tubers exhibited appreciable α- amylase inhibitory activity with an IC50 values 72.44µg/ml when compared with acarbose, IC50 value 83.23 ± 0.39 μg/mL and α - glucosidase inhibitory activity with an IC50 value of 28.96 µg / ml when compared with acarbose IC50 value 35.03 ± 0.24 μg/mL .This study supports the possible use of Dioscorea villosa tubers for diabetes because of its considerable α-amylase inhibitory activity as well as α - glucosidase inhibitory activity.